Daytime eccentric exercise and its impact on inflammatory markers and antioxidant defenses in physically active young men - Xu, Baikui; Guo, Shuai (Frontiers in Immunology, 2025)
BackgroundThe eccentric exercise performed during the day, whether in the morning or evening, may affect hormonal fluctuations and immune function. Furthermore, athletes frequently incorporate eccentric exercises into their training regimens or competitive events at these times, yet the inflammatory responses linked to this type of exercise remain unclear.AimThe aim of this study was to investigate the impact of day time (morning vs. evening) eccentric exercise on inflammatory cytokines, antioxidant enzymes, and hormonal responses in physically active men.MethodsUsing a randomized crossover design, twelve active men engaged in a session of plyometric type eccentric exercise (i.e., depth jump, 15 sets of 10 repetitions) in the morning and evening sessions, with blood samples collected pre (T1), immediately post (T2) and 1-h post-exercise (T3), to assess alterations in inflammatory cytokines (interleukin-6 [IL-6], IL-10, IL-1ra, and tumor necrosis factor alpha [TNF-α]), antioxidant enzymes (catalase [CAT], superoxide dismutase [SOD]), and glutathione peroxidase [GPx]), and hormonal changes (testosterone and cortisol).ResultsBoth the morning and evening eccentric exercise sessions indicated elevations in the cytokines with peak values at T2 (p=0.001), and enhancements of CAT and SOD with peaking values at T3 (p=0.001). While in the GPx, both the groups indicated their peaking elevations at the T2 (p=0.001). Morning group exhibited greater testosterone and cortisol concentrations than the evening group (p < 0.05), but these concentrations remained unchanged after the eccentric exercise session. A significant group × time interaction was observed in IL-6 (p=0.014), IL-10 (p=0.039), IL-1ra (p=0.001), TNF-α (p=0.021), CAT (p=0.046), SOD (p=0.001), GPx (p=0.016), testosterone (p=0.002) and cortisol (p=0.001), revealing greater changes for the evening compared to the morning exercise session.ConclusionsVariations in inflammatory cytokines, antioxidant enzymes, and hormonal responses to eccentric exercise in physically active young male are influenced by the time of day, with more pronounced responses observed in the evening than in the morning.